2023
DOI: 10.2147/ndt.s416271
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Factors Correlated with Postoperative Kinesiophobia in Patients with Cervical Spondylotic Myelopathy: A Cross-Sectional Survey

Abstract: Objective To investigate the prevalence of postoperative kinesiophobia in patients with cervical spondylotic myelopathy (CSM) and factors influencing the occurrence of kinesiophobia, to provide relevant basis for making clinical decisions for targeted interventions. Methods We enrolled a total of 85 patients who underwent CSM surgery at two grade-A general public hospitals in Fujian Province between September 2021 and May 2022. We conducted a questionnaire survey using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…State anxiety was defined as a total SAS score ≥50. 28 Among a Chinese population, study has shown that the sensitivity and specificity of the SAS ≥50 is 87% and 99%, respectively. 29 Study has also shown that the SAS has good reliability and validity (Cronbach’s α=0.75 and Kaiser-Meyer-Olkin=0.86, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…State anxiety was defined as a total SAS score ≥50. 28 Among a Chinese population, study has shown that the sensitivity and specificity of the SAS ≥50 is 87% and 99%, respectively. 29 Study has also shown that the SAS has good reliability and validity (Cronbach’s α=0.75 and Kaiser-Meyer-Olkin=0.86, respectively).…”
Section: Methodsmentioning
confidence: 99%